字典翻译 问答 其它 (a+2-2-a/4)÷(a/a-2)先化简,在求值(a-a²/a+b)(a/a-b-1)÷b²/a+b其中a=-2,b=-1(1)、1-1/x-5=x/x+5(2)、2/x+1-x/x²-1=0(3)、2x/x-y+2y/y-x(4)、x²/x+y-x+y(5)、先化简,在求值(3/x-1-1/x+1)÷x/
问题标题:
(a+2-2-a/4)÷(a/a-2)先化简,在求值(a-a²/a+b)(a/a-b-1)÷b²/a+b其中a=-2,b=-1(1)、1-1/x-5=x/x+5(2)、2/x+1-x/x²-1=0(3)、2x/x-y+2y/y-x(4)、x²/x+y-x+y(5)、先化简,在求值(3/x-1-1/x+1)÷x/
问题描述:

(a+2-2-a/4)÷(a/a-2)

先化简,在求值(a-a²/a+b)(a/a-b-1)÷b²/a+b其中a=-2,b=-1

(1)、1-1/x-5=x/x+5(2)、2/x+1-x/x²-1=0(3)、2x/x-y+2y/y-x(4)、x²/x+y-x+y

(5)、先化简,在求值(3/x-1-1/x+1)÷x/x²-1其中x=2

就这么多,过程要详细,在线,拜托了

崔庆权回答:
  [a+2-﹙2-a﹚/4]÷[a/﹙a-2﹚]   =[a+2-﹙2-a﹚/4]×﹙a-2﹚/a   =﹙a²-4﹚/a+﹙a-2﹚²/﹙4a﹚   =a-4/a+a/4-1+1/a   =5a/4-3/a-1   [﹙a-a²﹚/a+b][a/﹙a-b-1﹚]÷b²/﹙a+b﹚   =
点击显示
其它推荐
热门其它推荐
  • 其它